The Plasma Proteome Fingerprint Associated with Circulating Carotenoids and Retinol in Older Adults. Issue 1 (22nd September 2021) - Yamaguchi, Yuko; Zampino, Marta; Tanaka, Toshiko; Bandinelli, Stefania; Moaddel, Ruin; Fantoni, Giovanna; Candia, Julián; Ferrucci, Luigi; Semba, Richard D
ABSTRACT: Background: Although diets rich in carotenoids are associated with reduced risks of cardiovascular disease, age-related macular degeneration, disability, and other adverse aging outcomes, the underlying biological mechanisms are not fully elucidated. Objectives: To characterize the plasma proteome fingerprint associated with circulating carotenoid and retinol concentrations in older adults. Methods: In 728 adults ≥65 y participating in the Invecchiare in Chianti (InCHIANTI) Study, plasma α-carotene, β-carotene, β-cryptoxanthin, lutein, zeaxanthin, and lycopene were measured using HPLC. The SOMAscan assay was used to measure 1301 plasma proteins. Multivariable linear regression models were used to examine the relationship of individual carotenoids and retinol with plasma proteins. A false discovery rate approach was used to deal with multiple comparisons using a q-value < 0.05. Results: Plasma β-carotene, β-cryptoxanthin, lutein, zeaxanthin, and lycopene were associated with 85, 39, 4, 2, and 5 plasma proteins, respectively, in multivariable linear regression models adjusting for potential confounders (q < 0.05). No proteins were associated with α-carotene or retinol. Two or more carotenoids were positively associated with ferritin, 6-phosphogluconate dehydrogenase (decarboxylating), hepcidin, thrombospondin-2, and choline/ethanolamine kinase. The proteins associated with circulating carotenoids were related to energy metabolism, sirtuin signaling, inflammation and oxidative stress, iron metabolism, proteostasis, innate immunity, and longevity. Conclusions: The plasma proteomic fingerprint associated with elevated circulating carotenoids in older adults provides insight into the mechanisms underlying the protective role of carotenoids on health.